Effect of Metal Catalysts on Synthesis of Carbon Nanomaterials by Alcohol Catalytic Chemical Vapor Deposition - Worawut Muangrat; Supanit Porntheeraphat; Winadda Wongwiriyapan (My University, 2013)
Carbon nanomaterials (CNMs) were synthesized by alcohol catalytic chemical vapor deposition (CVD) at atmospheric pressure using different metal catalysts (Ni, Co and Fe) at a growth temperature of 700 °C.Ni and Fe acted as active catalysts for multiwalled carbon nanotubes (MWNTs) growth, while Co acted as an active catalyst for bamboo-like MWNTs and carbon nanofibers (CNFs) growth.The CNMs synthesized from Ni catalyst showed the highest crystallinity with a small amount of by-products.These results imply that metal catalyst is a key parameter to the structure, morphology and crystallinity of CNMs.The different effects of metal catalysts on the growth of CNMs can be explained in terms of the difference in the change in Gibbs free energy of metal carbide formation.
Keywords: Nanomaterials; Carbon fibers; Carbon Nanotubes in Composites